The Moderating Role of Environmental Investment on The Relationship of Environmental Responsibility and Firm Value - Rizki, Tabah (Wahana Riset Akuntansi, 2025)
Abstract Purpose – This study aims to investigate the effect of environmental responsibility (ER) on firm value and explore the moderating role of environmental investment (EI) on the relationship between them.Design/methodology/approach – This research uses quantitative method. The research data were taken from 399 observations of public energy and mining companies in ASEAN-5 during the period 2017-2019. Data processing was carried out using a panel data approach and multiple regression.Findings – The results of the study indicate that environmental responsibility can significantly increase firm value. Then, environmental investment has a significant positive effect on firm value. However, environmental investment has not proven to be able to provide a moderating effect on the relationship between environmental responsibility and firm valueOriginality/value –  This paper presents an original and timely contribution to the ongoing discussion about the role of environmental responsibility (ER) and environmental investment (EI) in enhancing firm value, particularly within the context of ASEAN-5 countries—Malaysia, Indonesia, the Philippines, Singapore, and Thailand. While existing studies on ER and its effect on firm value have largely focused on developed countries, the exploration of this relationship within the ASEAN-5 context is novel. The ASEAN-5 region is a critical area for examining these dynamics because of its unique economic and environmental challenges, and this research aims to provide empirical evidence on how ER and EI practices impact firm value in these countries.Research limitations/implications – This research still used secondary data, the number of observations were still limited. This research has policy implications for governments in each country, namely that they must strengthen the enforcement of regulations regarding companies' obligations to carry out environmental expenditures and that companies must actively participate and continue to develop green practices.